Becoming self-sufficient: a longitudinal person-centered analysis of financial identity and adult status during emerging adulthood. Issue 2 (3rd April 2023) - Serido, Joyce; Sorgente, Angela; Lanz, Margherita; Shim, Soyeon
ABSTRACT: Because finances play an important part in managing the demands of adult social roles, we investigate the formation of financial identity and its association with perceived adult status. Drawing from Marcia's (1966) operationalization of four identity statuses (i.e., foreclosed, achieved, diffused, moratorium) and adapted to the financial domain, we performed Latent Transition Analysis (LTA) using longitudinal data gathered from a cohort of college students in the United States at four time points (N = 672) covering an eight-year period (2008–2016). A key study finding is empirical directional evidence of financial identity as a predictor of adult status. In addition, findings show that, over time, individuals commit more strongly to a certain financial identity, which may in turn factor significantly in the process of achieving adult self-sufficiency. Finally, we distinguish three distinct financial identity profiles based on the way that participants made decisions related to financial matters during the transition to adulthood.